PENGARUH INFLASI, SUKU BUNGA, PROFITABILITAS DAN STRUKTUR MODAL TERHADAP HARGA SAHAM PERUSAHAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERCATAT DI BURSA EFEK INDONESIA - Sorta Angelia Br Aritonang; Yohana Priskawati Priskawati; Lasma Ria Tampubolo; Eka Mayastika Sinaga (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to obtain empirical evidence about the effect of inflation and interest rates on stock prices partially or simultaneously and to determine the most dominant variable that affects the stock price of property and real estate companies on the Indonesia Stock Exchange in 2018-2022. This type of research is quantitative research and the type of data used is quantitative secondary data derived from the results of the Indonesia Stock Exchange publication, about issuer data, reports published by Bank Indonesia, reference books, the internet, and other scientific scientific literature related to the topic of research discussion. Secondary data in this study includes monthly panel data for the period 2018-2022 which includes Debt To Equity Ratio (DER), Return On Equity (ROE), and Stock Price data taken from the Indonesia Stock Exchange website. While Inflation data, Interest Rates (BI Rate) are taken through the Bank Indonesia website. The data collection method is carried out by collecting supporting data from literature, journals, and reference books to get the case of the problem under study and collecting relevant secondary data from reports published by Bank Indonesia and the Indonesia Stock Exchange. The results of this study indicate that simultaneously the inflation rate and interest rate variables have a significant effect on the stock price of property and real estate companies on the Indonesia Stock Exchange and partially show that the inflation rate has a positive and significant effect on stock prices, while interest rates have no significant effect on stock prices.